Country Partnership Framework for Hashemite Kingdom of Jordan for the Period FY17-FY22 - World Bank; International Finance Corporation; Multilateral Investment Guarantee Agency (World Bank, Washington, DC, 2016)
The Government of Jordan, the World Bank Group (WBG), and the international community are working towards a paradigm shift in their collective response to the refugee crisis - a holistic approach which stresses the continuum between the humanitarian response and the country’s development agenda. In parallel, Jordan’s implicit social contract by which the state provided citizens with jobs and heavily subsidized public services is evolving. strategic engagement, the WBG will adopt a two-pronged approach aimed at simultaneously addressing Jordan’s immediate needs in view of the fluid and worsening regional situation while keeping a medium and long-term development commitment built on reforming the economy to create the right environment for inclusive, job-creating growth. The first pillar of the Country Partnership Framework (CPF) aims to foster the conditions for stronger private-sector-led growth and better employment opportunities for all.The second pillar of the CPF aims to improve the quality and equity of service delivery, including through private sector solutions.The CPF will implement the new Middle East and North Africa (MENA) Strategy at the country level.The CPF aligns with the Government’s vision Jordan 2025, the Executive Development Plan 2016-2018 (EDP), and the Sustainable Development Goals (SDGs).The CPF’s principles of engagement will be selectivity, flexibility, adaptability and partnership. The outlook for 2016 forecasts growth at three percent on account of a growing mining and quarrying sector, some energy investments, and base effect of the tourism and construction sectors, although some downside risks have begun to materialize in early 2016.